2006
DOI: 10.1103/physrevlett.96.111102
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational-Wave Extraction from an Inspiraling Configuration of Merging Black Holes

Abstract: We present new techniqes for evolving binary black hole systems which allow the accurate determination of gravitational waveforms directly from the wave zone region of the numerical simulations. Rather than excising the black hole interiors, our approach follows the "puncture" treatment of black holes, but utilzing a new gauge condition which allows the black holes to move successfully through the computational domain. We apply these techniques to an inspiraling binary, modeling the radiation generated during … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
828
0
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,130 publications
(847 citation statements)
references
References 14 publications
3
828
0
6
Order By: Relevance
“…For physically motivated excision conditions, one imposes apparent horizon or isolated horizon boundary condition to the conformal factor at the excised sphere so as these spheres become automatically horizons [30,31]. Alternatively one can use the puncture method to produce accurate initial data as the ones used in binary black holes evolutions [4,5,6,7,8], and black hole/neutron star binary simulations [32]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For physically motivated excision conditions, one imposes apparent horizon or isolated horizon boundary condition to the conformal factor at the excised sphere so as these spheres become automatically horizons [30,31]. Alternatively one can use the puncture method to produce accurate initial data as the ones used in binary black holes evolutions [4,5,6,7,8], and black hole/neutron star binary simulations [32]. …”
Section: Discussionmentioning
confidence: 99%
“…Initial data set for binary black holes with a variety of black hole parameters, such as binary mass ratio, and black hole spins, or the binary black hole-neutron star data will become more useful considering the remarkable progress made recently for the inspiraling binary black holes simulations up to a few orbits near the innermost stable circular orbits [1,2,3,4,5,6,7,8]. Several groups have been achieved to construct binary black hole initial data successfully [9,10,11,12,13,14,15,16,17,18], (for earlier works, see [19]).…”
Section: Introductionmentioning
confidence: 99%
“…The past year, however, has seen dramatic progress, and at this point independent codes using very different approaches and techniques can reliably model the coalescence, merger and ring-down of binary black holes [17][18][19][20][21]. Some of these calculations [18,19,21] treat the black hole singularity with the so-called puncture method [22] (see also [23,24]). Given that puncture initial data for binary black holes are most easily constructed in the transversetraceless formalism (see [4] and compare [25,26]), this development has renewed some interest in transversetraceless initial data.…”
Section: Introductionmentioning
confidence: 99%
“…Under this basic assumption, Hughes and Blandford [175] found that, in general, coalescences of MBHs with random spin directions result in a broad remnant spin distribution; in particular, highly spinning MBHs tend to spin down. With the advent of numerical relativity [176][177][178], it is now possible to construct accurate mappings of initial-to-final BH spins following purely GW-driven coalescences [179]. In general, unless the two initial MBH spins and the binary orbital angular momentum are aligned, coalescences are unlikely to result in highly spinning MBHs.…”
Section: Black Hole Spin Evolution Channelsmentioning
confidence: 99%